Pengaruh Pendekatan STEAM Berbasis PjBL terhadap High Order Thinking Skills Peserta Didik - Widya Paramita; Yanti Fitria (Jurnal Penelitian Pendidikan IPA, 2025)
The focus of the research investigated the influence of the PjBL-based STEAM approach on the high order thinking skills of students in science learning on sound and light wave materials. The research conducted was a quantitative research using a quasi-experimental design involving two groups, namely the control group using conventional methods and the experimental group using the PjBL-based STEAM approach. The results showed that the experimental group that applied the PjBL-based STEAM approach experienced a significant improvement compared to the control group that used conventional learning. The increase in high order thinking skills in the experimental group was 67.32%. In contrast, the control group also showed an improvement, but in a low percentage of 28.43%. The t-test showed a significant difference (p = 0.000), and the N-gain analysis showed that the experimental group had a higher N-gain (69.3%) compared to the control group (29.3%). So that the application of the PjBL-based STEAM approach is more effective in improving high order thinking skills compared to conventional learning methods.